Wartime Kiss : Visions of the Moment in the 1940s - Nemerov, Alexander (Book collections on Project MUSE., 2013)
"Wartime Kiss is a personal meditation on the haunting power of American photographs and films from World War II and the later 1940s. Starting with a powerful reinterpretation of one of the most famous photos of all time, Alfred Eisenstaedt's image of a sailor kissing a nurse in Times Square on V-J Day, Alexander Nemerov goes on to examine an idiosyncratic collection of mostly obscure or unknown images and movie episodes--from a photo of Jimmy Stewart and Olivia de Havilland lying on a picnic blanket in the Santa Barbara hills to scenes from such films as Twelve O'Clock High and Hold Back the Dawn. Erotically charged and bearing traces of trauma even when they seem far removed from the war, these photos and scenes seem to hold out the promise of a palpable and emotional connection to those years. Through a series of fascinating stories, Nemerov reveals the surprising background of these bits of film and discovers unexpected connections between the war and Hollywood, from an obsession with aviation to Anne Frank's love of the movies. Beautifully written and illustrated, Wartime Kiss vividly evokes a world in which Margaret Bourke-White could follow a heroic assignment photographing a B-17 bombing mission over Tunis with a job in Hollywood documenting the filming of a war movie. Ultimately this is a book about history as a sensuous experience, a work as mysterious, indescribable, and affecting as a novel by W.G. Sebald"--